The cell structure and growth rate of three species of marine microalgae (Chlorella vulgaris, Tetraselmis chuii and Isochrysis sp.) before and after cryopreservation - Kader, Muna A. Omar Abdul; Mohd Basri, Aizatul Adzwa; Zulkifly, Shahrizim; Omar, Hishamuddin; Ismail, Ahmad (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2014)
Three species of marine phytoplankton Chlorella vulgaris, Tetraselmis chuii and Isochrysis sp. were cultured using Conway media in 20 °C with the light intensity of 90 μmol m-2s-1 and a photoperiod of 12:12 h L/D cycle. Cells were harvested in stages at logarithmic and stationary phases. Equilibration time for cyroprotectant exposure was 10 to 20 minutes before the samples was placed in the programmable freezer for a controlled rate of cooling at -1 °C /min. The temperature was reduced uniformly from 200C until it reaches -40 °C where the samples were maintained at this temperature for 30 minutes before direct immersion into liquid nitrogen at -196 °C. Samples were stored in liquid nitrogen for one week. Percentage of viable cells was relatively higher in the stationary phase for the three species that is 95.13 % for Chlorella vulgaris, 79.09 % for Isochrysis sp. and 69.36 % for Tetraselmis chuii. The growth rate of viable cells for Chlorella vulgaris a both logarithmic and stationary phases and Tetraselmis chuii at logarithmic phase showed insignificant differences (p > 0.05) before and after cryopreservation. Tetraselmis chuii of stationary phase and Isochrysis sp. of both phases gave significant differences (p < 0.05) for growth rate before and after cryopreservation due to photo-oxidation. The cell structure after cryopreservation showed disorganization and abnormality in the ultra-structure but this did not seem to affect the growth rate of the viable cells.